Социјалното претприемништво како модел за одржливи социо-економски промени - Голубовски, Горан (Економски факултет, УКИМ, Скопје, 2014)
In today’s world of neoliberal capitalism which uses globalization as a vehicle for the creation of new markets, the needs of the smaller groups are often neglected. On the other hand, the governments’ social programs which depend on the reduced government budgets, as a result of the recent global economic crisis, as well as the programs of the third sector, do not always effectively solve the current social problems. Social entrepreneurship represents the answer to these challenges, via the integration of the social aims which are united in the social mission with the market orientation, which serves for the achievement of the economic aims. This concept draws its social mission from the local context where it originates from and that is the reason why it solves the given problems in the society more efficiently. It is a question of a hybrid joint which borrows from both worlds of profitable business and unprofitable third sector to meet the needs of marginalized groups. In Republic of Macedonia there is minimal number of initiatives that can be called socio-entrepreneurial. Through the analysis of two of them, which as far as the correlation of social mission to market orientation is concerned they are two extreme ends of the learning concept, we set up the frame for the development of the social entrepreneurship here. Results of the study show that measures for development of the social entrepreneurship in Republic of Macedonia are needed, which would be aimed at: raising public awareness for this concept; changes in the laws that would enable creation of a legal frame for registration of these hybrids; institutional support via formation of bodies which would coordinate the socio-entrepreneurial sector and economic support through tax reliefs, participation in public purchases etc.
Social entrepreneurship as a model for sustainable socioeconomic changes
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Таки Фити.
Keywords: social entrepreneurship, social entrepreneurs, social enterprises, social mission, socioeconomic development, contextual dependence, local context, integrated value, marginalized groups